2021
DOI: 10.3390/biomedicines9050533
|View full text |Cite
|
Sign up to set email alerts
|

Endocan and Circulating Progenitor Cells in Women with Systemic Sclerosis: Association with Inflammation and Pulmonary Hypertension

Abstract: Background: Systemic sclerosis (SSc) is characterized by early vasculopathy and fibrosis in the skin, lungs, and other tissues. Vascular manifestations of SSc include Raynaud’s phenomenon, digital ulcers, and pulmonary artery hypertension (PAH). PAH is the second most common cause of mortality in SSc. Circulating CD34+ cells associated with cardiovascular health status in several conditions, including chronic immune-inflammatory disease. CD34+ cell numbers have been found inconstantly reduced in SSc. Endocan, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 78 publications
(118 reference statements)
1
20
0
1
Order By: Relevance
“…The latter finding could partially explain the absence of a notable relationship between MUST scores and caloric or macronutrient consumption. Moreover, this points to important non-dietary factors being involved in the appearance of weight loss in our study group [2][3][4]. In this respect, we obtained statistically significant connections with mRSS and other disease-related changes.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The latter finding could partially explain the absence of a notable relationship between MUST scores and caloric or macronutrient consumption. Moreover, this points to important non-dietary factors being involved in the appearance of weight loss in our study group [2][3][4]. In this respect, we obtained statistically significant connections with mRSS and other disease-related changes.…”
Section: Discussionsupporting
confidence: 64%
“…Systemic sclerosis (SSc) is a rare chronic autoimmune disease mainly characterized by microvasculopathy, together with a widespread fibrosis of the skin and viscera [1]. SSc patients demonstrate an abundance of risk factors for nutritional decline, including the presence of chronic inflammation and the progressive nature of disease-related multisystem involvement [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that typical skin manifestations such as fibrosis and, to a lesser extent, calcinosis cutis may reduce vitamin D synthesis and influence the other clinical manifestations in scleroderma patients, with differences between diffuse (dcSSc) and limited cutaneous SSc (lcSSc). A closer look at the potential association between levels of vitamin D and the clinical phenotype of SSc showed no significant difference in vitamin D or its active metabolite 25(OH)D levels, irrespective of the disease subtype, in the majority of studies [ 10 , 16 , 22 24 , 41 , 45 ]. However, An et al demonstrated lower serum vitamin D in SSc compared with healthy controls and in dcSSc compared to lcSSc.…”
Section: Discussionmentioning
confidence: 99%
“…Hypovitaminosis D is a general finding in scleroderma [ 3 5 , 9 , 10 , 13 , 15 , 16 , 21 , 25 , 27 , 34 , 35 ], and based on its pleiotropic effects, including its immunomodulatory, cardioprotective, and antifibrotic properties, low vitamin D status could influence the pathogenetic pathways activated in SSc [ 30 ]. Nevertheless, the association between abnormal vitamin D status and SSc onset, or any of its clinical manifestations, is still under debate [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation